Effects of Stoichiometry on the H2‐Storage Properties of Mg(NH2)2–LiH–LiBH4 Tri‐Component Systems. Issue 14 (31st May 2017) - Wang, Han; Cao, Hujun; Pistidda, Claudio; Garroni, Sebastiano; Wu, Guotao; Klassen, Thomas; Dorheim, Martin; Chen, Ping
Abstract: The hydrogen desorption pathways and storage properties of 2 Mg(NH2 )2 –3 LiH– x LiBH4 samples ( x =0, 1, 2, and 4) were investigated systematically by a combination of pressure composition isotherm (PCI), differential scanning calorimetric (DSC), and volumetric release methods. Experimental results showed that the desorption peak temperatures of 2 Mg(NH2 )2 –3 LiH– x LiBH4 samples were approximately 10–15 °C lower than that of 2 Mg(NH2 )2 –3 LiH. The 2 Mg(NH2 )2 –3 LiH–4 LiBH4 composite in particular began to release hydrogen at 90 °C, thereby exhibiting superior dehydrogenation performance. All of the LiBH4 ‐doped samples could be fully dehydrogenated and re‐hydrogenated at a temperature of 143 °C. The high hydrogen pressure region (above 50 bar) of PCI curves for the LiBH4 ‐doped samples rose as the amount of LiBH4 increased. LiBH4 changed the desorption pathway of the 2 Mg(NH2 )2 –3 LiH sample under a hydrogen pressure of 50 bar, thereby resulting in the formation of MgNH and molten [LiNH2 –2 LiBH4 ]. That is different from the dehydrogenation pathway of 2 Mg(NH2 )2 –3 LiH sample without LiBH4, which formed Li2 Mg2 N3 H3 and LiNH2, as reported previously. In addition, the results of DSC analyses showed that the doped samples exhibited two independent endothermic events, which might be related to two different desorption pathways. Abstract : On the right path : Hydrogen desorption pathways and storage properties of 2 Mg(NH2 )2 –3 LiH– x LiBH4 samples ( x =0, 1, 2, and 4) were investigated systematically. The thermodynamic and kinetic properties improved and the desorption pathways gradually changed by increasing the molar ratio of LiBH4 in 2 Mg(NH2 )2 –3 LiH– x LiBH4 systems (see figure).